Strategic Educational Management in the Age of Disruption: Integrating Innovation, Leadership, and Learning Excellence - Marlina, Reni; Furwanti, Erni; Krismayanti, Yanti; Adiningsih, Neni Utami (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The rapid advancement of digital technologies has significantly transformed the landscape of education, requiring institutions to adopt strategic approaches to remain adaptive and competitive. This study aims to analyze the role of strategic educational management in the age of disruption by integrating innovation, leadership, and learning excellence within a comprehensive framework. Employing a qualitative research design, this study utilizes a conceptual framework approach supported by an extensive literature review of relevant academic sources. Data were collected from peer-reviewed journal articles and analyzed using thematic analysis to identify key patterns and relationships among variables. The results indicate that digital disruption has shifted educational management from traditional administrative practices toward dynamic, data-driven, and technology-oriented strategies. Strategic educational management is found to enhance institutional adaptability, improve decision-making processes, and strengthen organizational performance. Furthermore, leadership emerges as a critical factor in facilitating innovation and managing change, while innovation in teaching and learning significantly contributes to improved student engagement and learning outcomes.